Dampak Pemberian Gadget Pada Anak Balita Di Desa Patemon Kecamatan Seririt - Putu Janiasih; Ketut Eka Larasati Wardana; Kadek Ayu Suarmini (Jurnal Kesehatan Medika Udayana, 2022)
Background: Children have become active consumers where many gadget products with various applications have made children their target market. Purpose: The purpose of the study to find out the impact of giving gadgets to children under five in Patemon Village, Seririt District. Methode: qualitative description, selected 5 respondents, 1 of them as key informant. Result: children under five in Patemon Village experienced symptoms of gadget addiction. This is due to the lack of time for parents for their children to play together. Conclusion: The impact that can occur when giving toddlers gadgets earlier is that children will tantrum if their cellphones are taken, there are disturbances in the sense of vision, children tend to shut themselves up when playing gadgets and parents' time with children is quite minimal.